Women e-commerce: Perspective in Bangladesh - Sultana, Farha; Akter, Amina (Journal of Management, Economics, and Industrial Organization, 2021)
E-commerce (Electronic commerce) is a big hit in today’s market. E-commerce is an abbreviation for electronic commerce. E-commerce is that the purchase and sale of products and services over the net. E-commerce is a term used to describe the shift from a regular market to a digital marketplace. It is a new era in business. As Bangladesh progresses toward becoming a digital Bangladesh, the participation of women in digital platform is tremendous over the past two centuries and their participation as digital entrepreneurs is inspiring. This noteworthy way of doing business is progressing admirably all over the world, and Bangladesh does too. The sample of the study was exploited using the convenient sampling technique. Primary information was collected using structured forms and the questionnaire consist of statements in Likert’s five-point scale and secondary data was collected using various types of journals, document, and paper cutting etc. The primary area contains a segment profile of the respondents, and the second section is a questionnaire designed to understand women's involvement in the E-commerce sector and their perspectives in Bangladesh. The focus of this study is to evaluate the present state of women's e-commerce in Bangladesh, as well as to investigate the components, and challenges, and to sort out those challenges: road to fix it. The results of this study showed that, Cyber security now drives online-based businesses, resulting in web users building trust in the digital world. Finally, everyone in the community must collabo
Keywords: E-commerce; digital market; women entrepreneurship; Facebook